METHODOLOGICAL FOUNDATIONS OF DEVELOPING PHONETIC COMPETENCE IN FOREIGN LANGUAGE TEACHING (KONFERENSIYA, 2026)
Phonetic competence plays a crucial role in the formation of overall communicative competence in foreign language learning. Accurate pronunciation, appropriate intonation, and phonological awareness significantly influence intelligibility and successful communication. This article examines the methodological foundations of developing phonetic competence in foreign language teaching. It analyzes key theoretical approaches, instructional principles, and effective teaching strategies aimed at improving learners’ phonetic skills. Special attention is given to the integration of phonetics into communicative language teaching and the use of modern educational technologies.